HUBUNGAN MINAT, SELF EFFICACY, DAN KEMAMPUAN DASAR MATEMATIKA PESERTA DIDIK DENGAN KEMAMPUAN PEMECAHAN MASALAH - Nur Ghita Shaleha; Tomo Djudin; Hamdani Hamdani (Universitas Tanjungpura, 2022)
This study aims to examine the relationship between the factors that affect students' problem abilities, namely interests, self-efficacy, and basic mathematical abilities. The form of research used is original research. The sample consisted of 90 students of class XI-IPA at SMA Negeri 2 Sungai Raya, and the research instruments used were questionnaires and description questions. The data obtained were then processed with the SPSS application, as follows: 1) interest contributed 0,42% in problem-solving skills 2) the relationship of self-efficacy contributed 32,02% in problem ability 3) the relationship between basic mathematical abilities contributed 63,96 % in the ability to handle problems 4) the relationship of interest, self-efficacy, and basic mathematical abilities together contributes 96,40% to the problem management ability, so there are two factors that relate to or affect problem ability while the other factor is not related . The coefficient of determination for these three factors is 40.1%, while the rest is seen by other factors. In general, there is a significant relationship between interests, self-efficacy, basic mathematical abilities and problem problem abilities. This research is expected to be a reference to improve the factors that affect the problem solving ability of students.